FROM COMPLIANCE TO COMPETITIVE EDGE: A FINANCE LEADER’S GUIDE TO IFRS S1 AND S2 - Kamal , Syed Safwan (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2025)
This paper examines the strategic and operational implications of implementing International Financial Reporting Standards (IFRS) S1 and S2, the sustainability disclosure standards introduced by the International Sustainability Standards Board (ISSB). These standards mark a pivotal shift in corporate reporting by integrating sustainability risks, especially climate-related factors, into mainstream financial disclosures, with a focus on enterprise value. Using a qualitative, literature-based methodology, the paper identifies key challenges including regulatory misalignment across jurisdictions, fragmented environmental, social, and governance (ESG) data systems, limited internal capabilities, and increased assurance expectations. In response, it proposes a phased implementation framework encompassing materiality assessment, data governance, cross-functional collaboration, and continuous improvement. The findings highlight CFOs as key drivers of sustainability reporting and its alignment with strategy and investor needs. Beyond compliance, IFRS S1 and S2 offer a strategic opportunity to enhance transparency, build stakeholder trust, and gain competitive advantage. The paper outlines practical implications for corporate leadership, governance structures, policymakers, and researchers, highlighting the need for convergence, assurance readiness, and ongoing capability development. Ultimately, these standards are not just regulatory requirements, they represent a new blueprint for how organizations define, measure, and communicate long-term value in an ESG-driven economy.